Composite indicators of development: the importance of dimensional weights - Moreira, S. B.; Simões, N.; Crespo, N. (Economia Global e Gestão, 2012)
Measuring and quantifying development makes increasing use of composite indicators. This raises the issue of the determination of the proper weighting of the various dimensions considered. Using a public-opinion survey conducted in Portugal, we evaluate the importance of the main dimensions of development and examine if the dimensional weights depend on the respondents’ individual characteristics such as gender, age, or educational level. The evidence suggests that both education and health regularly stand out as the most highly-rated factors.